Effects of Curcumin and Nanocurcumin on Biochemical Parameters, and Performance of Broiler Chickens under Physiological Stress - Fathi, M; Saidian , S; Baghaeifar , Z; Mardani, P; Zandiyah, Z; Mansory, G; Rezaee, V (Journal of the Hellenic Veterinary Medical Society, 2026)
This study aimed to evaluate the effects of curcumin and nanocurcumin on growth performance, antioxidant status, inflammatory response, and hematological changes in male broiler chickens subjected to experimentally induced stress via in-feed dexamethasone (DEX). A total of 400 one-day-old male Ross 308 chicks were randomly assigned to four groups: (1) a positive control (PC) group with no treatment, (2) a negative control (NC) group receiving 1.5 mg/kg DEX, (3) a group receiving 1.5 mg/kg DEX and 200 mg/kg curcumin (Cur), and (4) a nanocurcumin (Nano-Cur) group receiving 1.5 mg/kg DEX and 200 mg/kg nanocurcumin. Each group consisted of five replicates with 20 birds per replicate. Dietary supplementation with curcumin or nanocurcumin mitigated the adverse effects of DEX on body weight, feed conversion ratio, and mortality. During the stress period, Nano-Cur supplementation enhanced serum superoxide dismutase and glutathione peroxidase activity while reducing malondialdehyde levels. Additionally, Cur/Nano-Cur supplementation lowered serum total cholesterol, triglycerides, aspartate aminotransferase (AST), and alanine transaminase (ALT) levels, while increasing IgG and IgM compared to the NC group. Physiological stress affected serum levels of TNF-α and IL-8, while DEX increased IL-10 levels. However, dietary supplementation with curcumin or nanocurcumin reduced TNF-α and increased IL-8 and IL-10 levels. Furthermore, curcumin/nanocurcumin supplementation alleviated the adverse effects of DEX by decreasing heterophil counts and the heterophil-to-lymphocyte ratio, while increasing lymphocyte counts, hematocrit (HCT), and hemoglobin (HGB) levels. In conclusion, dietary curcumin and nanocurcumin supplementation can mitigate DEX-induced oxidative stress and inflammatory responses, supporting their potential role in improving stress resilience in broiler chickens